PENGARUH KEPERCAYAAN DIRI SISWA SMA YANG MENGIKUTI DAN TIDAK MENGIKUTI BIMBINGAN BELAJAR TERHADAP PRESTASI BELAJAR MATEMATIKA - Handayani, Prastika Putri; Fitrianti, Hariani; Taufik, Abdul Rachman (Program Studi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan Universitas Pattimura, 2023)
This research is an expostfacto research with a quantitative approach. The purpose of this study was to determine whether (1) the effect of self-confidence on the mathematics learning achievement of class X students of SMA Negeri 1 Merauke, (2) the effect of students who took and did not take tutoring on the mathematics achievement of class X students of SMA Negeri 1 Merauke, (3) the influence of the self-confidence of students who take and do not take tutoring on the mathematics achievement of class X students of SMA Negeri 1 Merauke. The sample in this study was 83 students in class X SMA Negeri 1 Merauke. The research instrument used was a self-confidence questionnaire, and the value of student achievement. Data collection techniques included distributing self-confidence questionnaires to find out the level of self-confidence of students taking and not taking tutoring classes, and administering math quizzes to determine student achievement. Research data were analyzed using descriptive analysis, and followed by inferential analysis. The results showed that (1) there was an effect of self-confidence on the mathematics learning achievement of class X students of SMA Negeri 1 Merauke with a significance value of 0.000 < 0.05, (2) there was an influence between students who took and did not take tutoring on students' mathematics learning achievement class X SMA Negeri 1 Merauke with a significance value of 0.006 < 0.05, and (3) there is an effect of self-confidence of students who take and do not take tutoring on mathematics learning achievement with a significance value of 0.000 < 0.05 with an effect of 39.5%.